Peran Brand Image dalam Meningkatkan Efektivitas Influencer Marketing dan Social Media Marketing terhadap Purchase Intention Konsumen - Haris Ihsanil Huda; Putri Pratiwi (CV. Aksara Global Akademia, 2026)
This study aims to analyze the influence of influencer marketing and social media marketing on consumer purchase intention, with brand image as a mediating variable. A quantitative approach was used in this study, involving 99 respondents selected purposively. Data collection was conducted through an online questionnaire with a Likert scale. Data analysis used SPSS 27 through a series of tests, including validity and reliability tests to ensure the research instrument was suitable for use, as well as multiple regression and Sobel mediation tests to test the hypotheses. The results of the analysis indicate that social media marketing has a positive and significant effect on consumer purchase intention. However, influencer marketing did not show a statistically significant effect. Interestingly, brand image was found to have a significant negative effect on purchase intention, but instead acted as a mediator, mediating the relationship between social media marketing and purchase intention. These findings indicate that although social media marketing can directly drive purchase intention, the role of brand image remains crucial in strengthening the effectiveness of digital marketing strategies. Thus, companies need to integrate efforts to build a positive brand image in every digital marketing campaign, especially through social media, to maximize its impact on consumer behavior.